Oxysterols and mechanisms of survival signaling. (June 2016) - Vurusaner, Beyza; Leonarduzzi, Gabriella; Gamba, Paola; Poli, Giuseppe; Basaga, Huveyda
Abstract: Oxysterols, a family of oxidation products of cholesterol, are increasingly drawing attention of scientists to their multifaceted biochemical properties, several of them of clear relevance to human pathophysiology. Taken up by cells through both vesicular and non-vesicular ways or often generated intracellularly, oxysterols contribute to modulate not only the inflammatory and immunological response but also cell viability, metabolism and function by modulating several signaling pathways. Moreover, they have been recognized as elective ligands for the most important nuclear receptors. The outcome of such a complex network of intracellular reactions promoted by these cholesterol oxidation products appears to be largely dependent not only on the type of cells, the dynamic conditions of the cellular and tissue environment but also on the concentration of the oxysterols. Here focus has been given to the cascade of molecular events exerted by relatively low concentrations of certain oxysterols that elicit survival and functional signals in the cells, with the aim to contribute to further expand the knowledge about the biological and physiological potential of the biochemical reactions triggered and modulated by oxysterols.